Advanced treatment techniques for industrial wastewater - Hussain, Athar; Ahmed, Sirajuddin 1967- (Advances in environmental engineering and green technologies (AEEGT) book series, 2019)
"This book addresses topics in Industrial wastewater treatment and disposal. It will cover the different aspects of environmental engineering related to water and wastewater treatment processes and systems and control studies as well as solid and hazardous waste management emerging from such industries"...